Permainan Lego (Parallel Play) terhadap Perkembangan Motorik Halus pada Anak Usia 3â€“6 Tahun - Andarwati, Siska Rahiliyah; Munir, Zainal; Siam, Wiwin Nur (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2020)
There are still many children there who use gross motor skills rather than fine motor skills. Play facilities and infrastructure to stimulate children's development are also lacking so that fine motor development is less stimulated. The aim of the study was to determine the effect of lego (parallel play) games on fine motor development in children aged (3-6 years) at TK Pertiwi Lojajar Bondowoso. The study design used the pre-experimental type one-group pretest-posttest type with a sample of 40 people with saturated sampling techniques. Then analyzed by the Paired t-test statistical test with a significance level of Î± â‰¤ 0.05. The statistical test results were p = 0,000 (p 0.05) which shows that there are differences in children's fine motor development before and after given a lego game (parallel play). Conclusion there is the influence of children's fine motor development before and after given lego games (parallel play) in the Pertiwi Lojajar Bondowos Kindergarten. It is expected that parents should pay attention to the development that occurs in children, one of which is fine motor skills. It is intended that parents can provide more and appropriate stimulation to children.Keywords : Lego (parallel play), fine motor development